1970
DOI: 10.13057/nusbiosci/n080105
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Antibacterial activity of Boesenbergia pandurata, Zingiber zerumbet and Solanum ferox extracts against Aeromonas hydrophila and Pseudomonas sp.

Abstract: Abstract. Hardi EH, Kusuma IW, Suwinarti W, Agustina, Nugroho RA. 2016. Antibacterial activity of Boesenbergia pandurata, Zingiber zerumbet and Solanum ferox extracts against Aeromonas hydrophila and Pseudomonas sp. Nusantara . This study evaluated the potential antibacterial activity of Boesenbergia pandurata, Zingiber zerumbet and Solanum ferox extracts against Aeromonas hydrophila and Pseudomonas sp. This paper aims to review the best concentration of the extract B. pandurata, Z. zerumbet and S. ferox to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Herbs are rich sources of immune-enhancing substances, herbal Immunostimulant in contrast to vaccines; it can be modulating the innate or nonspecific immune response. Herbal plant extracts have anti-bacterial activity against Aeromonas hydrophila and Pseudomonas [58]. The present study revealed that O. niloticus fed on 1% thyme and rosemary showed reducing in mortality rates (10%) after 6 th weeks feeding compared with (90%) mortality for controls Fig ( 1).…”
Section: Challenge Infectionmentioning
confidence: 49%
“…Herbs are rich sources of immune-enhancing substances, herbal Immunostimulant in contrast to vaccines; it can be modulating the innate or nonspecific immune response. Herbal plant extracts have anti-bacterial activity against Aeromonas hydrophila and Pseudomonas [58]. The present study revealed that O. niloticus fed on 1% thyme and rosemary showed reducing in mortality rates (10%) after 6 th weeks feeding compared with (90%) mortality for controls Fig ( 1).…”
Section: Challenge Infectionmentioning
confidence: 49%
“…Further, the plant extracts of Boesenbergia pandurata (BP) and Zingiber zerumbet (ZZ) from East Kalimantan have in vitro and in vivo antibacterial activity against A. hydrophila bacteria, while Solanum ferox (SF) has been found to be an antibacterial agent for P. fluorescens bacteria. Similarly, for the prevention and treatment of bacterial infections in tilapia, BP and ZZ are also effective for treating A. hydrophila and P. fluorescens infection 8, 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The challenge test was administered by using A. hydrophila (EA-01) and P. fluorescens (EP-02); the bacteria were appropriately prepared as per the method of Hardi et al . 6 , 35 The test was administered at Week 8, with 10 goldfish being exposed to a specific treatment; the fish were infected with the combined bacteria by means of intermuscular injection (0.1 mL each fish) of 10 5 CFU mL −1 of the bacteria at a 1:1 ratio. Subsequently, fish mortality was monitored from 24 h after the first injection until week 12.…”
Section: Methodsmentioning
confidence: 99%
“…The dose of BPE utilized in carp feed is 2, 4, 6 g kg À1 of fish feed, which is the dose used in tilapia tests. 5,6,10,30,35,48 Tilapia tests used this dose revealed an increase in growth and resistance to A. hydrophila and Pseudomonas sp. bacterial infections.…”
Section: Revised Amendments From Versionmentioning
confidence: 98%